2016
DOI: 10.1128/mcb.00950-15
|View full text |Cite
|
Sign up to set email alerts
|

Gtf2ird1-Dependent Mohawk Expression Regulates Mechanosensing Properties of the Tendon

Abstract: Mechanoforces experienced by an organ are translated into biological information for cellular sensing and response. In mammals, the tendon connective tissue experiences and resists physical forces, with tendon-specific mesenchymal cells called tenocytes orchestrating extracellular matrix (ECM) turnover. We show that Mohawk (Mkx), a tendon-specific transcription factor, is essential in mechanoresponsive tenogenesis through regulation of its downstream ECM genes such as type I collagens and proteoglycans such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 72 publications
2
62
0
Order By: Relevance
“…It is also reported that mechanical strain promotes the differentiation of MSCs into tenocytes in vitro (21,42). In this regard, we recently found that Gtf2ird1 translocates into the nucleus in response to mechanical strain and activates the Mkx promoter through chromatin regulation (43). Here, our mechanical stretch experiments with TDCs stimulation.…”
Section: Discussionmentioning
confidence: 52%
“…It is also reported that mechanical strain promotes the differentiation of MSCs into tenocytes in vitro (21,42). In this regard, we recently found that Gtf2ird1 translocates into the nucleus in response to mechanical strain and activates the Mkx promoter through chromatin regulation (43). Here, our mechanical stretch experiments with TDCs stimulation.…”
Section: Discussionmentioning
confidence: 52%
“…Given that both Mkx –/– rats as well as Mkx +/– and Mkx –/– mice develop ectopic bones in the Achilles tendons, it is possible that rare variants in the MKX gene might be a genetic predisposing factor for Achilles tendon ossification in humans. Recent studies have shown that Mkx expression in tendon cells is regulated by mechanical strain through the Gtf2ird1 transcription factor and that mechanical stimulation caused cultured Mkx –/– mutant, but not wild‐type, tendon cells to undergo chondrogenic differentiation . Furthermore, it has been shown that the inflammatory cytokine IL‐1β strongly suppressed MKX gene expression in cultured human anterior cruciate ligament (ACL)‐derived cells and that MKX expression was significantly reduced in degenerated ACL in osteoarthritis patients .…”
Section: Discussionmentioning
confidence: 99%
“…Tenocytes respond to mechanical strain by increasing collagen production, and mechanical signals promote MSC differentiation into tenocytes . Mechanical stimulation also promotes collagen fiber thickening along with increased fiber density …”
Section: Developmental Biology Of Tendon and Ligament Tissues And Cellsmentioning
confidence: 99%
“…Mkx is also responsive to mechanical stimulation both in vitro and in vivo. In moderate treadmill exercise, the effects of mechanical loading on collagen fiber thickening are not observed in Mkx‐deficient mice, suggesting that Mkx is critical in the response to mechanical stimuli . Interestingly, general transcription factor II‐I repeat domain‐containing protein 1 (Gtf2ird1) was found to play an important role in translating mechanical stress to Mkx expression .…”
Section: Developmental Biology Of Tendon and Ligament Tissues And Cellsmentioning
confidence: 99%
See 1 more Smart Citation